Effective energy storage from a triboelectric nanogenerator - Yunlong Zi (Nature Portfolio, 2016)
Self-charging systems based on the connection of a nanogenerator and an energy storage unit through a rectifier can have low energy storage efficiencies. Here, the authors design the charging cycle to maximize the energy storage efficiency of a triboelectric nanogenerator by introducing a motion-induced switch.